THE SCOPE OF ISLAMIC EDUCATION MANAGEMENT AND LEADERSHIP WITH A QUALITATIVE APPROACH METHOD - Romli, Ombi; Herianto, Ii Puji; Muttaqin, Zainal; Syarifudin, Encep; Muslihah, Eneng (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This research discusses the scope of management and leadership in Islamic education using a qualitative approach. The main focus of this research is to understand how management and leadership systems are applied in Islamic educational institutions, as well as to identify the challenges faced in their management. The research method used is a qualitative-descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that effective management of Islamic education must be based on Islamic principles, such as the values of monotheism, justice, and the welfare of the ummah. In addition, leadership in Islamic education must prioritize morals and exemplary in order to create a conducive learning environment. It was also found that the main challenges in Islamic education management include limited resources, lack of professionalism in management, and resistance to innovation. By understanding the strategic role of management and leadership in Islamic education, it is hoped that Islamic educational institutions can optimize their performance and quality of education